(untitled) (Revista Brasileira Multidisciplinar, 2023)
Dioctophyme renale is a renal nematode parasitic on dogs, wild carnivores, and occasionally other mammals and humans, acquired through ingestion of the parasite’s larvae through paratenic hosts or intermediate hosts such as Lumbriculus variegatus. Clinical signs vary between hematuria, lack of appetite, low back pain, or they may be asymptomatic. Diagnostic methods consist of blood count, biochemical, radiography, ultrasound and urinalysis tests. Nephrectomy of the affected kidney is the most recommended treatment, when the organ has been affected, however, nephrotomy can be performed to remove the parasites when there is still preservation of the organ. This work aims to report the occurrence of this nematode in a 1-year-old mixed breed (SRD) dog, weighing 8.5 kg, who would be neutered. On physical examination, no abnormalities were observed, the blood count showed leukocytosis with increased neutrophil rods, lymphocytes and eosinophils, and ultrasound examination revealed structures suggestive of Dioctophyme renale, occupying a large part of the right kidney. Therefore, the surgery for ovariosalpingohisterctomia (OSH) and total right nephrectomy were performed. The animal was sedated and submitted to inhalation anesthesia and laparotomy, and between OSH and nephrectomy, a free parasite was seen in the abdominal cavity. Three more nematodes were found in the right kidney after surgery, and the animal recovered well from the surgery, and after ten days, the stitches were removed. Despite an asymptomatic condition, leukocytosis and ultrasound images were suggestive of renal dioctofimosis.